Nuevos aportes al conocimiento de las migraciones de peces en el Río Paraná - Bonetto, Argentino A.; Canón Verón, Marta; Roldán, Dante (Ecosur, 2023)
Studies on fish migration in the Paraná River were performed during the period 1975-1981, mainly in the join of Paraná and Paraguay Rivers, as well as the High Paraná, based on capturing, tagging and releasing of fishes. Lea's hydrostatie tag was used to mark fish, obtained by netting to avoid capture injuries. Resulta are as follows: - Registered migratory tendencies of Charaeoids fish confirm as a general rule, previous statements on the literature about the Paraná and tributaries. - Data obtained on other Charaeoids and Siluroids, permit to clarify unknown aspeets of their behaviour. - Obtained data are partially contradicting with Godoy’s statements on fish migration in the Upper Paraná, but agree with other authors’ results on the Middle and Lower reach. So, two main kinds of migratory behaviour are shown: one related to breeding in which fish are recorded to move long distances, is the “active migrants” ecotype. The other referred to species intermixed with the above mentioned, in which fish do not require a great displacement for that purpose, is of the "passive migrants" ecotype. It seems to be a high proportion of passive migrants among fish populations in the river reaches studied, particularly in the Middle Paraná River.